THE ROLE OF ELECTRONIC WORD OF MOUTH (E-WOM) IN MEDIATING THE INFLUENCE OF SOCIAL MEDIA PROMOTIONS ON ONLINE PURCHASING DECISIONS(Study on consumers of Jamu Rahsa Nusantara) - Ketut Ayu Surya Manika Sari; Gede Suparna (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Online shopping has become a new habit for Indonesian people, and its development continues to increase from year to year. Consumer purchasing decisions often begin by studying information obtained from social media and online reviews. Jamu Rahsa Nusantara in March – July received an increasing number of negative reviews, and this had an impact on consumer purchasing decisions. This research aims to analyze the role of Electronic Word of Mouth (e-WOM) in mediating the influence of social media promotions on online purchasing decisions among Jamu Rahsa Nusantara consumers. The research method used is quantitative with data collection methods through surveys based on questionnaires to Jamu Rahsa Nusantara consumers in Denpasar who have made online purchases. The total sample was 140 respondents, using a non-probability sampling technique with a purposive sampling method. Path analysis techniques are used to examine the relationship between social media promotions, e-WOM, and purchasing decisions. The research results found that social media promotion had a significant and positive effect on e-WOM; e-WOM has a significant and positive effect on decisionsonline purchases; e-WOM mediates the influence of social media promotions on purchasing decisions.